Optimising colorectal cancer screening strategies and target populations in budget-constrained regions through cost-effectiveness analysis: a case from eastern China - Hao Li; Peng Zhang; Yun Fu; Weibing Wang; Ao Xu (BMJ Open)
Objectives The primary aim of this study was to optimise colorectal cancer (CRC) screening strategies and target populations in resource-limited areas through cost-effectiveness analysis, evaluating the best screening methods and appropriate screening ages.Design A prospective microsimulation model was used for cost-effectiveness analysis, calibrated with real-world data.Setting The study was conducted in Huzhou City, Zhejiang Province, China, focusing on primary and secondary healthcare levels. Data were obtained from the Huzhou Center for Disease Control and Prevention.Participants The study included 418 805 local residents who participated in the Huzhou screening programme between 2020 and 2022. Inclusion criteria were individuals aged 45–100 years and residing in the local area.Interventions Four initial screening methods were evaluated: single-sample immunochemical faecal occult blood test (iFOBT), double-sample iFOBT, single-sample iFOBT combined with a risk assessment questionnaire and double-sample iFOBT combined with a risk assessment questionnaire. Screening frequencies included annual and biennial intervals.Primary outcome measures The primary outcome measure was the cost per incremental quality-adjusted life year (QALY) for different screening strategies. Also, the impact on CRC incidence, related deaths, life years saved (LYS) and QALYs was considered.Results The primary data were sourced from the Huzhou screening programme, which included 418 805 individuals from 2020 to 2022. All screening strategies were found to be effective, with the cost per incremental QALY being less than $1036, which is below the minimum standard for middle-income countries. The most effective screening strategy was the annual combined two-sample iFOBT and risk evaluation questionnaires. This approach led to a reduction in CRC incidence and related deaths by 2435 and 1174 cases per 100 000 individuals, respectively, and an increase in LYS by 13 903 years and QALYs by 35 564 years. The recommended ages to begin and end screening were 48 and 72 years, respectively.Conclusions All CRC screening strategies demonstrated effectiveness compared with non-screening, with the annual combined two-sample iFOBT and risk evaluation questionnaires emerging as the optimal approach. For additional regions, the best screening strategy can be selected based on the health outcomes and costs we have provided.